Productivity Analysis On Company Xyz Using The Production, Organization, Sales, Product, Arbeiter, Capital (Pospac) Method - Ida Ayu Kade Sintya Yulianti Dewi; I Ketut Satriawan; Lutfi Suhendra (International Journal of Economics, Business and Innovation Research, 2025)
XYZ company experienced raw material failures that did not meet the company’s quality standards from February to December 2024, resulting in a 10.1% decrease in production and the company continues to suffer losses. This study aims to: (1) measure the level of productivity in production, organization, sales, products, labor, and capital; (2) analyze the factors causing the low productivity index; and (3) provide improvement recommendations to increase the company’s productivity. The Production, Organization, Sales, Product, Arbeiter, and Capital (POSPAC) method is used to measure productivity, while the fishbone diagram is applied to identify and analyze problem causes. The results from January to December 2024 show the greatest decline occurred in the sales element in March -39.430, while the smallest decline was in the product element in January -0.230. The key factors contributing to low productivity are inconsistent raw material quality, absence of quality control, lack of training and competency development, and no HR development programs related to finance. To enhance productivity, the company should establish raw material standards (color, aroma, moisture content), create a coffee quality control SOP based on these standards, conduct training to improve competencies in production, finance and assess the quality of raw materials.